Ereth's birthday - Avi; Floca, Brian (New York HarperCollins, 2000)
Feeling neglected on his birthday, Ereth, the cantankerous old porcupine, sets out looking for his favorite treat and instead finds himself acting as "mother" to three young fox kits.
610L
77037
Keywords: Porcupines -- Juvenile fiction; Foxes -- Juvenile fiction; Animals -- Juvenile fiction; Parent and child -- Juvenile fiction